IDENTIFIKASI DAN UJI SENSITIVITAS Staphylococcus aureus TERHADAP ANTIBIOTIK DARI SAMPEL ULKUS PASIEN DIABETES MELITUS DI RSUD Dr. MOEWARDI - Masita, Tutus Elsa; Puspawati, Nony; Rahmat Budi Nugroho (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2023)
The prevalence of Diabetes Mellitus in Indonesia is increasing, Uncontrolled blood glucose levels may lead to diabetic ulcers, which in turn can lead to peripheral neuropathy. The bacterium Staphylococcus aureus is a possible source of this illness. Staphylococcus aureus has become a major health risk due to the rise in bacterial resistance to many classes of antibiotics, making sensitivity testing imperative. The purpose of this investigation is to identify Staphylococcus aureus in ulcer samples from RSUD Dr. Moewardi's diabetic patients and to investigate their susceptibility to various antibiotics. This type of research is an analytic observational approach cross sectional namely research to determine the sensitivity of bacteria to antibiotics by the diffusion method with Kirby-Bauer discs. This research was conducted by isolating bacteria Staphylococcus aureus in ulcer samples of patients with diabetes mellitus and then tested for sensitivity to antibiotics. The results of the ulcer sample isolation showed that out of 10 samples there were 4 positive ulcer samples Staphylococcus aureus. Sensitivity test results show that Staphylococcus aureus 100% sensitive to the antibiotics Ciprofloxacin, Imipenem, Gentamicin, and Vancomycin, 90% sensitive to the antibiotic Erythromycin, while 10% is intermediate to the antibiotic Erythromycin